2018
DOI: 10.3168/jds.2018-14454
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of crude extracts from actinomycetes against mastitis pathogens

Abstract: The emergence of antimicrobial resistance to commonly used antibiotics has necessitated the development of new antimicrobial products. Crude extracts produced by actinomycetes contain antimicrobial metabolites that can inhibit bacterial growth. The objective of our study was to evaluate the antimicrobial activity of crude extracts (Caat1-54 and CaatP5-8) produced by actinomycetes against isolates of Staphylococcus aureus, Staphylococcus chromogenes, Streptococcus dysgalactiae, and Streptococcus uberis, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Due to the low amount and instability of compound 39, only compound 43 was tested for antimicrobial and cytotoxic activities at concentrations ≥ 66.66 µg/mL, and the results indicate that 43 did not show any antimicrobial activity against Staphylococcus aureus [15]. Consequently, the antibacterial activity in Figure 1 at t R : 10.50-11.30 min can be linked to kenalactam B (39).…”
Section: Hplc-uv-hresims Analysis Of Crude Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the low amount and instability of compound 39, only compound 43 was tested for antimicrobial and cytotoxic activities at concentrations ≥ 66.66 µg/mL, and the results indicate that 43 did not show any antimicrobial activity against Staphylococcus aureus [15]. Consequently, the antibacterial activity in Figure 1 at t R : 10.50-11.30 min can be linked to kenalactam B (39).…”
Section: Hplc-uv-hresims Analysis Of Crude Extractsmentioning
confidence: 99%
“…The two tubes were shaken for 20 min, followed by a centrifugation step at 9000 rpm for 10 min. The ethyl acetate was evaporated at 40 • C using a rotary evaporator, and the residue was dissolved in 1 mL of methanol and then centrifuged at 14,000 rpm for 10 min [39].…”
Section: Preparation Of Crude Extractmentioning
confidence: 99%
“… 169 , 170 Animal feed containing microbial extracts and probiotics can be regarded as an efficient technique for treating cow mastitis. 171 , 172 Few research has stated that how probiotics taken orally affect the bovine mastitis. It was demonstrated that oral treatment of L. casei Zhang and L. plantarum P-8 drastically decreased SCC and increased milk production.…”
Section: Treatmentmentioning
confidence: 99%
“…Staphylococcus aureus (n = 20) was isolated from mammary quarter milk samples of cows affected by clinical (n = 11; 11 herds) and subclinical (n = 9; 9 herds) mastitis in commercial dairy herds (n = 15) located in Southeast Brazil. These isolates were obtained from previous studies (Leite et al, 2018;Tomazi et al, 2018) and selected due to their resistance (or multiresistance) to antimicrobials commonly used for mastitis treatment (our unpublished data). The Staph.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…A volume of 10 µL of standardized bacterial solution was applied in each well (except for broth sterility controls); the plates were covered and homogenized at 200 rpm for 10 min on a stirring table (Quimis) and then incubated at 37°C. After 18 h, 30 µL of 0.05% thiazolyl blue tetrazolium bromide (MTT; Sigma-Aldrich) was added to the plates for MIC determination by visual inspection (Leite et al, 2018).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%